Adherence To Lifestyle Modifications Among Patients Attending Diabetes Management Clinics: A Comprehensive Evaluation - Shabaa, Ahmed S.; Muhieldeen, Mohammed A. Ameer; Alghazali, Abdullah M.; Alshibly, Haider Warid; Almehnh, Husam (Academia Open, 2026)
General Background: Type 2 diabetes mellitus remains a major global public health challenge, and lifestyle modification is considered a fundamental component of diabetes management. Specific Background: Despite strong clinical recommendations regarding dietary regulation and physical activity, adherence to lifestyle modification among patients with type 2 diabetes remains inconsistent, particularly in resource-limited settings. Knowledge Gap: Limited evidence is available regarding the determinants of dietary and exercise adherence among Iraqi patients with type 2 diabetes, particularly when examined through the PRECEDE model framework. Aims: This study aimed to evaluate adherence to dietary and exercise recommendations and identify sociodemographic, clinical, and behavioral factors associated with adherence among patients attending a tertiary diabetes management clinic in Al-Najaf, Iraq. Results: A descriptive cross-sectional study involving 412 patients revealed substantial differences between dietary and exercise adherence. Good dietary adherence was reported by 60.9% of participants, whereas only 3.2% achieved good exercise adherence and 81.8% demonstrated poor exercise adherence. The aggregate PRECEDE score showed a weak positive correlation with exercise adherence. Older age, absence of formal education, lower body mass index, longer diabetes duration, and rural residence were identified as independent predictors of optimal dietary adherence. Novelty: The study separately examined dietary and exercise adherence using the PRECEDE model within an Iraqi tertiary diabetes care setting, highlighting distinct determinants of each behavior. Implications: The findings emphasize the urgent need for barrier-specific physical activity interventions, stronger social reinforcement mechanisms, and integrated lifestyle support strategies to improve diabetes self-management outcomes. Keywords : Type 2 Diabetes Mellitus, Lifestyle Modification, Dietary Adherence, Exercise Adherence, PRECEDE Model Key Findings Highlights Dietary compliance was considerably higher than participation in recommended physical activity. Social reinforcement emerged as the weakest behavioral determinant among participants. Rural residence, older age, longer disease duration, lower body mass index, and lack of formal schooling were associated with better nutritional compliance.